Mashups Concepts, Models and Architectures - Daniel, Florian; Matera, Maristella; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Mashups have emerged as an innovative software trend that re-interprets existing Web building blocks and leverages the composition of individual components in novel, value-adding ways. Additional appeal also derives from their potential to turn non-programmers into developers. Daniel and Matera have written the first comprehensive reference work for mashups. They systematically cover the main concepts and techniques underlying mashup design and development, the synergies among the models involved at different levels of abstraction, and the way models materialize into composition paradigms and architectures of corresponding development tools. The book deliberately takes a balanced approach, combining a scientific perspective on the topic with an in-depth view on relevant technologies. To this end, the first part of the book introduces the theoretical and technological foundations for designing and developing mashups, as well as for designing tools that can aid mashup development. The second part then focuses more specifically on various aspects of mashups. It discusses a set of core component technologies, core approaches, and architectural patterns, with a particular emphasis on tool-aided mashup development exploiting model-driven architectures. Development processes for mashups are also discussed, and special attention is paid to composition paradigms for the end-user development of mashups and quality issues. Overall, the book is of interest to a wide range of readers. Students, lecturers, and researchers will find a comprehensive overview of core concepts and technological foundations for mashup implementation and composition. Even without low-level coding details, practitioners like software architects will find guidance on key implementation concepts, architectural patterns, and development tools and approaches. A related website provides additional teaching material which can be used either as part of a course or for self study.
1 Introduction -- Part I Fundamentals -- 2 Data and Application Integration -- 3 Web Technologies -- 4 Model-Driven Software Development -- Part II Mashups -- 5 Mashup Components -- 6 Mashups -- 7 Advanced Mashups -- 8 Tool-Aided Mashup Development -- 9 Mashups and End-User Development -- 10 Quality in Mashup Development -- 11 Outlook.
Keywords: Computer science; Software engineering; Computer Science; Information Systems Applications (incl. Internet).; Software Engineering